Urna de cristal como canal digital de participación ciudadana en Colombia - Amaya-Rodríguez, John Edickson; Gonzalez-Sanabria, Juan Sebastian; Castro-Romero, Alexander (Revista Científica, 2017)
In this paper is described the current regulations in Colombia concerning to the e-government. It also refers to the different tools used by the glass urn strategy Colombian government. Its scope is also assessed in both citizenship reports published by this strategy, as well as through a survey in all the departments. Finally, some recommendations that can be considered in the development of the activities of the selected channel with the objective to expand the coverage of the channel and can be an effective approach of citizens to government through technological tools are proposed.